Motif Dan Kepuasan Penonton Terhadap Program LAPOR PAK! di Desa Tanra Tuo, Kabupaten Pinrang - Muhammad Sidiq; Iskandar Iskandar; Sulvinajayanti Sulvinajayanti; Wahyuddin Wahyuddin (IAIN Padangsidimpuan, 2025)
This study examines the motives and audience satisfaction with the Lapor Pak! program in Tanra Tuo Village, Pinrang Regency, focusing on the dimensions of information, personal identity, social integration, and entertainment. This phenomenon arose due to the high popularity of Lapor Pak! which combines comedy, satirical humor, and social issues, and its influence on rural communities that have not been affected by similar programs. The main objective of this study is to understand the factors that encourage viewers to watch Lapor Pak! and the level of satisfaction they feel related to these dimensions. The research method used was a quantitative approach with a survey design, where data was collected using a questionnaire measured on a 1-5 Likert scale. Validity and reliability tests were conducted to ensure that the instrument used could provide accurate and consistent results, with the validity test results showing all items were valid and reliability was very high (Cronbach's Alpha 0.9). The findings of the study show that entertainment motives dominate viewer motivation (average 4.275), followed by information motives (4.043), personal identity (3.687), and social integration (3.542). The level of audience satisfaction is also highest in the entertainment dimension (4.197), followed by information (3.965), personal identity (3.629), and social integration (3.588). The significance of this finding lies in Lapor Pak!‘s ability to fulfill viewers’ emotional and informational needs, although its function in identity formation and social integration is more supportive. The findings have merit in providing insights into how entertainment programs on television can serve as tools to reduce stress, provide social insights, and strengthen personal values among rural audiences, as well as contributing to the study of Uses and Gratification theory in the context of local communities